Rapid Study on Mefloquine Hydrochloride Complexation with Hydroxypropyl-β-Cyclodextrin and Randomly Methylated β-Cyclodextrin: Phase Diagrams, Nuclear Magnetic Resonance Analysis, and Stability Assessment - Amaury Durand; David Mathiron; Sébastien Rigaud; Florence Djedaini-Pilard; Frédéric Marçon (Pharmaceutics, 2023)
This study investigates the complexation of mefloquine hydrochloride by cyclodextrins to improve its solubility in order to design an oral solution. This approach may enhance the effectiveness of mefloquine, a drug which can be used for malaria prophylaxis and treatment in children. Mefloquine hydrochloride’s solubility was assessed in different buffer solutions, and its quantification was achieved through high-performance liquid chromatography. The complexation efficiency with cyclodextrins was evaluated, and nuclear magnetic resonance (NMR) methods were employed to determine the interactions between mefloquine and cyclodextrins. Mefloquine’s solubility increased when combined with hydroxypropyl-β-cyclodextrin (HP-β-CD) and randomly methylated β-cyclodextrin (RAMEB), with RAMEB being more effective. The drug’s solubility varied across different pH buffers, being higher in acidic buffers. Interestingly, mefloquine’s solubility decreased with a citrate buffer, possibly due to precipitation. The NMR studies highlighted non-covalent interactions between RAMEB, HP-β-CD, and mefloquine, explaining the solubilizing effect via complexation phenomena. Furthermore, the NMR experiments indicated the complexation of mefloquine by all the studied cyclodextrins, forming diastereoisomeric complexes. Cyclodextrin complexation improved mefloquine’s solubility, potentially impacting its bioavailability.